Signs and symbols as a critical art issue (Знак и символ как искусствоведческая проблема) - Личман, Елена Юрьевна; Иванова, Александра Аркадьевна (Культурное наследие Сибири, 2019)
Essence of definitions of “symbol” and “sign” is being uncovered in this article; analysis of common semantic structure of a symbol is conducted. The authors concludes that imaginary-signed form possesses wide specter of meaning, reflecting the world in unity of sensitive, emotional and rational; conscious and unconscious; common, special and unique (Раскрывается сущность понятий «символ» и «знак», проводится анализ общесмысловой структуры символа. Авторы приходят к выводу, что образно-знаковая форма имеет широкий спектр значения, отражая мир в единстве чувственного, эмоционального и рационального; сознательного и бессознательного; общего, особенного и единичного).